Life-history variation, environmental fluctuations and competition in ecologically similar species: modeling the case of rotifers. (18th September 2015) - Gabaldón, Carmen; Montero-Pau, Javier; Carmona, María José; Serra, Manuel
Abstract : Competition for resources can lead to species exclusion. However, this exclusion may be avoided if species show differential adaptation to physical environment. Empirical studies on competition are difficult when species are phylogenetically close and have complex life cycles. This is the case of B. plicatilis and B. manjavacas, two cryptic rotifer species differing in their salinity niches and in life-history traits related to sex and diapause. These differences have been suggested to promote the stable co-occurrence observed in natural populations of these species. However, in a previous empirical study, the outcome of competition between both species was always exclusion. Here, we theoretically explored the effect of complex life-history traits and salinity fluctuations on the long-term competitive outcome of B. plicatilis and B. manjavacas . We developed a model and simulated ecological scenarios combining different growing period lengths, levels of crossed induction of sex between species and salinity regimes. Results show that a fluctuating salinity regime, an intermediate length of growing season and a low level of crossed induction of sex are essential conditions to take into account to explain coexistence.